Delicious pâté from your local free-range mum. - Cloake, Felicity (New Statesman, 2017)
The article discusses cannibalism in relation to diet practices and beliefs. Topics include the book "Eat Me," by Bill Schutt, health reasons for the practice of cannibalism, and the deaths of South Fore tribe members in Papua New Guinea from the disease kuru. The practice of placentophagy, eating a placenta after childbirth, is noted.